PROTOCOL OPTIMIZATION OF RT-qPCR FOR NF-ΚB DETECTION IN CARDIAC TISSUE FROM HFHS-FED MICE - Jaya, Ferdinand Wiliam; Novita, Bernadette Dian; Suwandito, Laurensius; Wijaya, Hendy; Tjahjono, Yudy; Hendrata, Adi Pramono; Dewi, Sianty; Wijaya, Sumi; Ervina, Martha; Kuncorojakti, Suryo (JURNAL WIDYA MEDIKA, 2026)
Accurate detection of gene expression in challenging tissues requires methodological optimization to ensure reproducibility. Cardiac tissue, with its low cell density and variable RNA yield, presents particular difficulties for RT‑qPCR analysis. This study aimed to refine NF‑κB detection in HFHS‑fed C57BL/6 mice by comparing a standard 2‑ΔΔCt approach with an optimized protocol incorporating individualized calibrators adjusted for RNA concentration. Six male mice were divided into standard-diet (STD) and high‑fat, high‑sucrose (HFHS) groups, and cardiac RNA was extracted after 8 weeks of feeding. While relative NF‑κB expression trends were higher in the HFHS group, differences were not statistically significant; however, the optimized method consistently reduced variability and improved measurement reliability compared to the generalized approach. These findings highlight the value of individualized calibration as a protocol refinement for RT‑qPCR, offering a more rational framework for gene expression analysis in heterogeneous or technically demanding tissue samples.